2020
DOI: 10.1108/ijssp-05-2020-0157
|View full text |Cite
|
Sign up to set email alerts
|

Being bisexual in contemporary Italy: between stigma and desire of visibility

Abstract: PurposeThe Italian sociological scientific community has shown a limited interest in issues related to bisexuality. The purpose of this paper is to fill the knowledge gap on the subject, showing data of an empirical research conducted online on the Italian bisexual community.Design/methodology/approachThe article is based on a mixed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Several Italian studies have reported that Italian SGM individuals experience high levels of oppression and victimization due to their non-heterosexual orientation or gender nonconformity (e.g., Baiocco, Nardelli, Pezzuti, & Lingiardi, 2013;Bochicchio et al, 2019;Lingiardi et al, 2016;Lingiardi, Baiocco, & Nardelli, 2012;Monaco, 2020;Prunas et al, 2015;Scandurra et al, 2018). Thus, these studies depict the Italian context as unsupportive for SGM individuals.…”
Section: Heteronormativity In the Italian Social Contextmentioning
confidence: 97%
“…Several Italian studies have reported that Italian SGM individuals experience high levels of oppression and victimization due to their non-heterosexual orientation or gender nonconformity (e.g., Baiocco, Nardelli, Pezzuti, & Lingiardi, 2013;Bochicchio et al, 2019;Lingiardi et al, 2016;Lingiardi, Baiocco, & Nardelli, 2012;Monaco, 2020;Prunas et al, 2015;Scandurra et al, 2018). Thus, these studies depict the Italian context as unsupportive for SGM individuals.…”
Section: Heteronormativity In the Italian Social Contextmentioning
confidence: 97%
“…Non-heterosexual identities and behaviors have been viewed as morally reprehensible, deviating from a normal development, a sign of an artistic personality or a private matter which should not be spoken about (Baiocco et al, 2013;Capozzi & Lingiardi, 2003). Despite the undoubted progress made in recent years (e.g., Lingiardi et al, 2015;Scandurra et al, 2019Scandurra et al, , 2020aScandurra et al, , 2020b, Italy continues to show a limited support for LGBT individuals, who still experience high levels of oppression and victimization, a general delay in the recognition of their civil rights, and a lack of anti-discrimination legislation for their protection (Amodeo et al, 2018;Baiocco et al, 2013;Bochicchio et al, 2019;Lingiardi et al, 2015;Monaco, 2020;Scandurra et al, 2018). In this regard, many LGB older people who have spent their youth and early adulthood in Italy tend to conceal their sexual identity in offline contexts (Pietrantoni et al, 2000;Scandurra et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Petrocchi et al [ 28 ] found among 327 Italian lesbian, gay, and bisexual individuals that bisexual people exhibited lower levels of self-awareness, community connectedness, authenticity, and intimacy than their lesbian and gay counterparts. Monaco [ 29 ] found in a sample of 218 Italian bisexual individuals that they had great difficulty coming out because they felt they were not understood by others and argued that these individuals perceived the Italian context as strongly heteronormative. The most comprehensive study of minority stress among bisexual people in Italy was conducted by Scandurra et al [ 30 ], who found that discrimination and internalized stigma were positively associated with poorer health, that internalized stigma mediated the association between discrimination and mental health problems, but that resilience did not moderate this latter association.…”
Section: Introductionmentioning
confidence: 99%